Rice Cookers, Social Media, and Unruly Women: Disentangling Electricity's Gendered Implications in Rural Nepal - Matinga, Margaret N.; Gill, Bigsna; Winther, Tanja (Frontiers in Energy Research, 2019)
Rice cookers, social media, and television sets are commonly used in rural Nepal. In this paper we explore how gender norms condition the uptake of these artifacts, and the gendered implications of their uses. We draw on material from a household survey, in-depth interviews, focus group discussions, and key informant interviews, collected in 2017 in Dhading and Tanahun districts in rural Nepal. The results show that each of the three artifacts initiate distinct, gendered dynamics in terms of uptake, uses, and effects. Women's use of electric rice cookers aligns with their gendered identity as cooks, helping them improve their gendered work and do not trigger resistance from men. In contrast, the use of mobile phones, social media, and television, prompt complex gender outcomes, resistances, and negotiations. Young people use social media to initiate self-negotiated marriages, shunning arranged marriages thus increasing their agency. It was reported that these self-negotiated marriages tend to be earlier (ages 12–14) than before, as young girls drop out of school to marry their chosen partners, thus threatening their empowerment. Access to television and internet has increased awareness about family planning methods, but persistent gender hierarchies hinder women from freely deciding on and accessing these methods. Women and youth pursuing new opportunities that challenge gender norms are sometimes labeled as unfaithful and unruly by others in the villages. The paper highlights the need to understand subversive responses to social and cultural changes mediated by electricity so that policy and practice can support the desired social transformations.